2015
DOI: 10.1186/s12992-015-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

Policy implications of medical tourism development in destination countries: revisiting and revising an existing framework by examining the case of Jamaica

Abstract: BackgroundMedical tourism is now targeted by many hospitals and governments worldwide for further growth and investment. Southeast Asia provides what is perhaps the best documented example of medical tourism development and promotion on a regional scale, but interest in the practice is growing in locations where it is not yet established. Numerous governments and private hospitals in the Caribbean have recently identified medical tourism as a priority for economic development. We explore here the projects, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…In the CAC region, medical tourism is understood to be a solution to address unused capacity in the private health sector (21, 22). For Guatemala and Mexico, this capacity already exists and is seeking utilization; for Barbados, the demonstrated viability of tapping into the international market to reach a sufficient catchment of private patients is facilitating planning for new private facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CAC region, medical tourism is understood to be a solution to address unused capacity in the private health sector (21, 22). For Guatemala and Mexico, this capacity already exists and is seeking utilization; for Barbados, the demonstrated viability of tapping into the international market to reach a sufficient catchment of private patients is facilitating planning for new private facilities.…”
Section: Discussionmentioning
confidence: 99%
“…While existing discussion of international hospital accreditation focuses on its role as a marketable credential and means to improve and standardize quality of care, many participants emphasized international hospital accreditation as a precursor to accessing private insurance funds outside of their countries. International hospital accreditation should thus be understood not only as an emerging standard of care, but also as a precursor to scaling up flows of international patients into the future (21, 26). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guatemala is not alone in this regard. Findings from our other studies exploring medical tourism sector development in the LAC region have demonstrated similar tension between the potential for regulation and the will to actually regulate, including in Barbados [ 14 ], Jamaica [ 38 ], St. Lucia [ 39 ], and Cayman Islands [ 40 ]. Although our Guatemalan informants generally recognized the need for governments to regulate public health care, opinions on regulation of medical tourism were mixed.…”
Section: Discussionmentioning
confidence: 95%
“…The healthcare provider and staff are a significant factor in Malaysia [15]. In the same way, the healthcare workforce, health insurance and the international accreditation have been confirmed to have great impact on medical tourism in Jamaica [16].…”
Section: Medical Tourismmentioning
confidence: 96%